PENGARUH PEMBELAJARAN DI SEKOLAH ALAM TUNAS MULIA TERHADAP KETERAMPILAN DALAM MENINGKATKAN EKONOMI SISWA - Daru Susanti (Develop: Jurnal Ekonomi Pembangunan, 2021)
This study aims to find out the effect of learning at the Alam Tunas Mulia school, Bantar Gebang on skills in improving student economics. There are three research questions that the researcher summarizes based on the field survey at the school, namely; 1. How are the environmental conditions and facilities of the Alam Tunas school in support of learning economic skills. 2. How are the effects of catfish, duck, chicken, and hydroponic farming facilities to improve the skills of students and schools 3. How can catfishes, ducks, chickens, and hydroponic farming facilities improve the economy of students and schools Researchers found answers to research questions based on the data obtained that the effect of learning at Tunas Mulia school on skills in improving student economics, there are elements that support this result, namely the existence of three curriculums that are applied, namely; 1. The Tahfidz Curriculum. 2. The School of Nature Curriculum. 3. Curriculum packages A and B.